Vasculitis Pathogenesis: Can We Talk About Precision Medicine? - Ozen, Seza; Batu, Ezgi Deniz (Frontiers in Immunology, 2018)
Precision medicine is designing the medical care by taking into account the individual variability for each person. We have tried to address whether the existing data may guide precision medicine in primary systemic vasculitides (PSV). We have reviewed GWAS data, lessons from monogenic mimics of these diseases and biomarker studies in immunoglobulin A vasculitis/Henoch Schönlein purpura, Kawasaki disease, ANCA-associated vasculitis, polyarteritis nodosa (PAN), Takayasu arteritis, and Behçet’s disease (BD). Genome-wide association studies provide insights about the pathogenesis of PSV while whole exome sequencing studies lead to discovery of monogenic vasculitides, phenotype of which could mimic other types of vasculitis such as PAN and BD. Monogenic vasculitides form a subgroup of vasculitis which are caused by single gene alterations and discovery of these diseases has enabled more specific therapies in these patients. With increasing number of studies on biomarkers, new targets for treatment appear and better and structured follow-up of PSV patients will become possible. Proteomics and metabolomics studies are required to better categorize our patients with PSV so that we can manage them appropriately and offer more targeted therapy.